Trust management V 5th IFIP WG 11.11 International Conference, IFIPTM 2011, Copenhagen, Denmark, June 29 - July 1, 2011. Proceedings - IFIPTM (Conference) Copenhagen, Denmark) 2011; Wakeman, Ian; SpringerLink (Online service). (New York Springer, 2011)
This book constitutes the refereed proceedings of the 5th IFIP WG 11.11 International Conference, IFIPTM 2011, held in Copenhagen, Denmark, in June/July 2011. The 14 revised full papers and 8 short papers presented together with the abstracts of 4 keynote talks were carefully reviewed and selected from 42 submissions. The papers feature both theoretical research and real-world case studies from academia, business and government focusing on areas such as: trust models, social and behavioral aspects of trust, trust in networks, mobile systems and cloud computation, privacy, reputation systems, and identity management.
Electronic reproduction.
Keywords: Computer security -- Congresses; Data encryption (Computer science) -- Congresses; Computer networks -- Security measures -- Congresses; Electronic books